2016
DOI: 10.1111/epi.13333
|View full text |Cite
|
Sign up to set email alerts
|

Patients' expectations and experiences of epilepsy surgery—A population‐based long‐term qualitative study

Abstract: SUMMARYObjective: The aim of this prospective and population-based longitudinal study was to explore patients' expectations before surgery and their experiences both short and long term after epilepsy surgery. Methods: A national sample of adult patients answered open-ended questions preoperatively, 2 years after surgery and at a cross-sectional long-term follow-up (mean 13 years, standard deviation [SD] 1.85). The answers were analyzed by qualitative content analysis. Results: Eighty patients participated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 32 publications
2
27
1
1
Order By: Relevance
“…The timing of a return to driving is in part dictated by local medicolegal regulations; however, few patients delayed regaining their driver's license beyond 24 months. A recent qualitative study of the long-term outcomes of epilepsy surgery identified a similar process to that described by our cohort, 9 supporting an active reframing and reprioritization of ongoing progress postsurgery, in order to maintain psychosocial "equilibrium" as patients work toward achieving their social goals. 33 Pleasingly, the number of patients who had achieved driving (87%) and new employment outcomes (51%) exceeded estimates of patients who expected these outcomes in a previously published TLE cohort from Austin Health (45% and 35%, respectively).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The timing of a return to driving is in part dictated by local medicolegal regulations; however, few patients delayed regaining their driver's license beyond 24 months. A recent qualitative study of the long-term outcomes of epilepsy surgery identified a similar process to that described by our cohort, 9 supporting an active reframing and reprioritization of ongoing progress postsurgery, in order to maintain psychosocial "equilibrium" as patients work toward achieving their social goals. 33 Pleasingly, the number of patients who had achieved driving (87%) and new employment outcomes (51%) exceeded estimates of patients who expected these outcomes in a previously published TLE cohort from Austin Health (45% and 35%, respectively).…”
Section: Discussionsupporting
confidence: 74%
“…[2][3][4] Research has identified a number of common expectations held by patients regarding their postsurgical outcomes. [7][8][9] Such expectations often reflect important social milestones that individuals may have felt impeded in attaining as a result of their epilepsy. [7][8][9] Such expectations often reflect important social milestones that individuals may have felt impeded in attaining as a result of their epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance safety, restricted ambulation of patients, guard rails, specially designed bathrooms, specific nursing, and technician support and standardized operating procedures for the treatment of status epilepticus are compulsory in many EMUs (Dobesberger et al, 2017;Kobulashvili et al, 2016;Rosenow et al, 2016;Spanaki et al, 2012;Spritzer et al, 2015). Former research findings indicate that EMU patients are tense and feel anxious, bored, depressive and less than clean (Andrewes, Camp, Kilpatrick, & Cook, 1999;Bristol, Natarajan, Lin, & Malow, 2001;Egger-Rainer, Trinka, Höfler, & Dieplinger, 2017;Ozanne, Graneheim, Ekstedt, & Malmgren, 2016). Enhancing patient comfort is an essential outcome of nursing (Kolcaba, 1992) in this setting.…”
mentioning
confidence: 99%
“…For example, unrealistic expectations, such as expecting surgery to make you more clever or skilful at work, have been found to negatively impact post-surgical HRQOL, whereas patients with more achievable expectations are more likely to consider surgery a success (Baxendale and Thompson, 1996;Wilson et al, 1999). For both adults and parents of children who undergo epilepsy surgery, dissatisfaction is consistently related to psychiatric, behavioural or neurological complications of the surgery (Keene et al, 1998;Sajobi et al, 2014;Ozanne et al, 2016). This provides clear red flags for clinicians to consider when working with patients having surgery.…”
Section: Behavioural Mood and Adjustment Difficulties Following Surgerymentioning
confidence: 99%